On the quasi-static and impact responses of aluminum honeycomb under combined shear-compression. (September 2019) - Hou, B.; Wang, Y.; Sun, T.F.; Liu, J.G.; Zhao, H.
Highlights : A Rotatable Hopkinson bar is proposed for the impact shear-compressive behavior of cellular material with separated normal and shear responses. Numerical works indicate that this method provides a quite accurate measurement of forces and deformations in both shear and normal directions. The impact and quasi-static shear-compressive tests are performed on a 5052 honeycomb at different loading angles. The normal strength of the honeycomb decreases with the increasing loading angle, while the shear strength changes oppositely. An elliptical envelope with lateral expansion from quasi-static to dynamic is found to describe the average crushing strength of honeycomb. Abstract: A new Rotatable Hopkinson bar is proposed for investigating the impact shear-compressive behavior of cellular materials with separated normal and shear responses. Validating works by numerical simulations on the whole loading process indicates that this dynamic shear-compression method provides a quite accurate measurement on the specimen forces and deformation in both shear and normal directions. With this new design, the impact shear-compression responses of a 5052 honeycomb in TW plane are investigated at different loading angles and compared with the corresponding quasi-static results. Good reproducibility is achieved for most of the loading cases in terms of normal stress/normal displacement and shear stress/shear displacement curves, except the ones in which different deformation modes co-exist. The experiment results from both quasi-static and dynamic loadings reveal that the normal strength of the honeycomb will be weakened, but the shear strength becomes more important with an increasing shear deformation component. A crush envelope in elliptical shape is found to describe the average shear and compressive strengths of honeycomb for both quasi-static and dynamic loadings. The deformation modes of honeycombs under combined shear-compression are examined for all the testing results and some influencing factors, such as specimen dimensions, contact conditions and specimen geometric imperfections are confirmed.